A new approach to assessing the space use behavior of macroinvertebrates by automated video tracking. Issue 7 (13th March 2021) - Shokri, Milad; Cozzoli, Francesco; Ciotti, Mario; Gjoni, Vojsava; Marrocco, Vanessa; Vignes, Fabio; Basset, Alberto
Abstract: Individual space and resource use are central issues in ecology and conservation. Recent technological advances such as automated tracking techniques are boosting ecological research in this field. However, the development of a robust method to track space and resource use is still challenging for at least one important ecosystem component: motile aquatic macroinvertebrates. The challenges are mostly related to the small body size and rapid movement of many macroinvertebrate species and to light scattering and wave signal interference in aquatic habitats. We developed a video tracking method designed to reliably assess space use behavior among individual aquatic macroinvertebrates under laboratory (microcosm) conditions. The approach involves the use of experimental apparatus integrating a near infrared backlight source, a Plexiglas multi‐patch maze, multiple infrared cameras, and automated video analysis. It allows detection of the position of fast‐moving (~ 3 cm/s) and translucent individuals of small size (~ 5 mm in length, ~1 mg in dry weight) on simulated resource patches distributed over an experimental microcosm (0.08 m 2 ). To illustrate the adequacy of the proposed method, we present a case study regarding the size dependency of space use behavior in the model organism Gammarus insensibilis, focusing on individual patch selection, giving‐up times, and cumulative space used. In the case study, primary data were collected on individual body size and individual locomotory behavior, for example, mean speed, acceleration, and step length. Individual entrance and departure times were recorded for each simulated resource patch in the experimental maze. Individual giving‐up times were found to be characterized by negative size dependency, with patch departure occurring sooner in larger individuals than smaller ones, and individual cumulative space used (treated as the overall surface area of resource patches that individuals visited) was found to scale positively with body size. This approach to studying space use behavior can deepen our understanding of species coexistence, yielding insights into mechanistic models on larger spatial scales, for example, home range, with implications for ecological and evolutionary processes, as well as for the management and conservation of populations and ecosystems. Despite being specifically developed for aquatic macroinvertebrates, this method can also be applied to other small aquatic organisms such as juvenile fish and amphibians. Abstract : We developed a video tracking method designed to reliably assess space use behavior among individual aquatic macroinvertebrates.To illustrate the utility of the proposed method, we present a case study regarding the size dependency of space and resource use behavior in Gammarus insensibilis, focusing on individual's patch selection, giving‐up time, and cumulative space used .We observed the negative size dependency of individual giving‐up time, showing that patch departure occurred sooner in larger individuals than smaller ones and that individual cumulative space used scaled positively with body size.